JOINT SPECTRUM KOLEKSI OPERATOR PADA RUANG HILBERT (JOINT SPECTRUM OF A COLLECTION OF OPERATORS ON A HILBERT SPACE) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT In this paper we study some properties of the Joint Spectrum of a collection of bounded linear operators on a Hilbert Spaces. First of all, if A is a unital commutative Banach Algebra and A' is its dual, we define subsets '6A of the dual space A'. The Joint Spectrum of subset (TA of the operator algebra A, is defined as set ({ h( TA,)} : h e QA} . Most of the results, we adopted from Dekker (1969) and Folland (1995).